Shadow and laughter: the comicality in the Shadow Theater (Móin-Móin Magazine - Studies in the Art of Puppetry, 2022)
This study aims to instigate discussions about the relationship between Shadow Theater and comicality. We identified, from the analysis of scenes, shows and performances of/with shadows produced in the last four decades in our country, that there are few Shadow Theater experiences based on derision. Would the shadow or laughter be opposite phenomena? To reflect on such questioning, we initially discuss artistic experiences of Shadow Theater in Brazil and in the world that present links or are based on comicality and then we list some hypotheses that would justify why the relationship between shadow and laughter is little explored in our country.
Keywords: Shadow theater; comicality; shadow; laugh